La cosecha de Agua en la microcuenca Chacomas, y su impacto sobre la disponibilidad del Recurso Hìdrico, en La Comunidad Cuajinda, Sector Huacamarcanga, Distrito de Quiruvilca, Provincia de Santiago de Chuco, Región La Libertad - Calderón Urquiza, Edwin Gilmer (2017)
The pace of global population growth, pollution, the use and less sustainable water use and the phenomena associated with climate change, make the access to this resource will be even more limited and unstable. It is thus that water resource management projects using the technique of water harvesting have been implemented in Freedom, with the purpose of monitoring its proper functioning. The present work was to evaluate, technically, the water harvesting in the Chacomas watershed, as well as its social impact. Was made technical visits in 15 areas with treatment of the project area to check their characteristics; measurement was carried out in 3 points in areas with treatment versus 3 points in adjacent areas without treatment with similar dimensions and characteristics; and surveys were applied in the three beneficiary sectors. The design and implementation of the project was carried out under the technical criterion known and accepted, however, the abandonment of the areas where the water is damaging their functioning and consequently its assessment. According to the capacity monitored, on average, the flows provided by the areas with treatment presented an increase of 49.35% on the areas without treatment. Finally, the project did not have the same impact in all three sectors beneficiaries; the rural sectors of the Chacomas appear with the best positive impact, this is what 66.67% of its settlers, while in the urban sector of Santiago de Chuco Huacamarcanga sector and the positive impact is 24.2% and 36.3%, respectively.